Oxytocin, Postnatal Depression, and Parenting: A Systematic Review. Issue 1 (January 2016) - Mah, Beth L.
Abstract : Learning Objectives: After participating in this activity, learners should be better able to: Assess the effects of postnatal depression on parenting. Evaluate the relationships between oxytocin and postnatal depression. Assess the use of oxytocin to improve parenting. Objective: To carry out a systematic review exploring the interconnections between oxytocin, postnatal depression (PND), and parenting. Questions include: (1) How does PND affect parenting? (2) How does oxytocin affect parenting? (3) How does oxytocin affect PND? Methodology: To review English articles in major medical databases. Results: Compared to nondepressed controls, mothers with PND interact with their infants less sensitively, report feeling less competent, and less often choose recommended practical-parenting strategies. Psychological interventions for mothers with PND generally have positive effects on mother-infant interactions. The administration of oxytocin in community samples tends to improve parental behaviors. Findings exploring the association between oxytocin and PND were inconsistent, with some evidence that oxytocin has a negative impact on mood. Conclusions: Oxytocin is potentially useful in improving parental behaviors of mothers with PND, but more research is needed to establish its safety because of the uncertain impact of OT on maternal mood.